Efektifitas Pengolahan Kombinasi Elektrokoagulasi-Filtrasi Dalam Menyisihkan TSS dan COD pada Air Limbah Kawasan Industri - Felano Elga Bahctiar; Mohamad Mirwan (Jurnal Serambi Engineering, 2024)
Rapid industrial development in Indonesia has led to the establishment of numerous industrial zones, raising concerns about environmental pollution due to high levels of TSS and COD. Electrocoagulation is shownto be effective in removing TSS and COD by generating flocs through an electrochemical process, although these flocs can still pass through sedimentation processes. Filtration has been identified as a method to maximise the results of electrocoagulation. The aim of this research is to investigate the effect of adding NaCl salt to electrocoagulation treatment under flow system conditions and to evaluate the effectiveness of combining electrocoagulation and filtration under flow system conditions in removing TSS and COD from wastewater. Industrial wastewater was fed into an electrocoagulation reactor at a current intensity of 5 A and then continuously fed into filtration at a rate of 0.2 L/min. Aluminium electrodes and filtration media, namely quartz sand and activated carbon, are used. Research variables include NaCl salt addition (0; 0.2; 0.5) gram/L and sampling duration (80, 100, 120, 140) minutes. The results show that the addition of 0.5 g/l NaCl salt achieves a high TSS removal of 80.67% and COD removal of 62.04% at a sampling time of 100 minutes. The combination of electrocoagulation and filtration successfully removed 90.22% of TSS and 71.68% of COD.